2003
DOI: 10.1080/10635150390251063
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetics of Fanged Frogs: Testing Biogeographical Hypotheses at the Interface of the Asian and Australian Faunal Zones

Abstract: The interface of the Asian and Australian faunal zones is defined by a network of deep ocean trenches that separate intervening islands of the Philippines and Wallacea (Sulawesi, the Lesser Sundas, and the Moluccas). Studies of this region by Wallace marked the genesis of the field of biogeography, yet few workers have used molecular methods to investigate the biogeography of taxa whose distribution spans this interface. Some taxa, such as the fanged frogs of the ranid genus Limnonectes, have distributions on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
209
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 126 publications
(219 citation statements)
references
References 0 publications
8
209
1
1
Order By: Relevance
“…This isolation scenario seems to hold for some continental island dwelling amphibians: a recent study of fire salamanders showed a reduction of genetic diversity on insular populations indicating that these populations evolved in isolation without any subsequent marine dispersal events (Velo-Antón et al, 2012). However, some studies indicate that amphibians are in fact able to disperse to islands (Seppa and Laurila, 1999;Evans et al, 2003;Vences et al, 2003), although the exact mechanism of dispersal is unknown. In this study, we examine the population genetics of Thoropa taophora, a frog species endemic to the Atlantic Coastal Forest of Brazil (Feio et al, 2006) that inhabits rocky coastal shores and has some physiological tolerance to seawater (Bokermann, 1965;Sazima, 1971;Abe and Bicudo, 1991;Brasileiro et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This isolation scenario seems to hold for some continental island dwelling amphibians: a recent study of fire salamanders showed a reduction of genetic diversity on insular populations indicating that these populations evolved in isolation without any subsequent marine dispersal events (Velo-Antón et al, 2012). However, some studies indicate that amphibians are in fact able to disperse to islands (Seppa and Laurila, 1999;Evans et al, 2003;Vences et al, 2003), although the exact mechanism of dispersal is unknown. In this study, we examine the population genetics of Thoropa taophora, a frog species endemic to the Atlantic Coastal Forest of Brazil (Feio et al, 2006) that inhabits rocky coastal shores and has some physiological tolerance to seawater (Bokermann, 1965;Sazima, 1971;Abe and Bicudo, 1991;Brasileiro et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To date, every molecular genetic study that has broadly sampled populations across the range of a widespread frog species in Southeast Asia (southern China to Sulawesi) has uncovered genetic diversity interpreted by those authors as unrecognized species diversity (Toda et al 1998;Emerson et al 2000;Li et al 2001a,b;Matsui et al 2001;Veith et al 2001;Brown & Guttman 2002;Bain et al 2003;Evans et al 2003;Matsui et al 2005). Seven of these ten studies involved frog species that live only in intact forest.…”
Section: Cryptic Sympatric Southeast Asian Frogs B L Stuart and Omentioning
confidence: 99%
“…Cryptic fragmentation has been proposed on the Indonesian island of Sulawesi based on similar patterns of diversity in multiple groups, including the Celebes toad (Evans et al 2003c), monkeys (Evans et al 2003b), fanged frogs (Evans et al 2003a) and flying lizards (McGuire et al 2007). However, the validity of a demographic model of isolation by distance (IBD) plus fragmentation as opposed to a model of exclusively IBD has been questioned (Bridle et al 2004).…”
Section: Introductionmentioning
confidence: 99%